Rheological characterization of four Kansas hard red winter wheat flour-water dough systems - Steeples, Summer (Kansas State University, 2010)
Kansas is the top wheat-producing state, providing about 1/5 of the yearly wheat crop in the U.S. Therefore, the quality of wheat grown in Kansas is a primary concern of the milling and baking industry. Quality of wheat flour is measured through analysis of protein, dough rheology, and baked product characteristics. This study characterized four commonly-grown Kansas hard red winter wheat cultivars chosen to span the largest possible range of protein contents and baking qualities. Flour protein content and moisture was determined by NIR, and composition was assessed using SE-HPLC. Dough empirical rheological and mixing characteristics were determined by farinograph and mixograph recording dough mixers. Rheological measurements of fundamental dough properties were performed through strain sweeps, frequency sweeps, temperature sweeps, creep-relaxation, and stress relaxation on a rheometer. All cultivar flours were baked to assess baking quality through evaluation of loaf volume, texture profile analysis (TPA), C-cell, and x-ray microtomography (XMT). Overley and Karl 92 have the two highest protein contents, respectively, and are not significantly different in percent of unextractable polymeric protein (UPP). Generally, cultivars with higher protein and percent UPP (Overley and Karl 92) gave larger loaves, much more expanded air cells, thinner cell walls, greater void fractions, and better mixing properties. Lower TPA firmness was found for Overley, corresponding with its larger XMT fragmentation index, existence of large air cells, and high void fraction. In contrast, 2137 gave the lowest XMT fragmentation index, low void fraction, larger cell wall thicknesses, and a significantly firmer (P< 0.05) crumb structure. Protein content was found to have an inverse relationship with the elastic nature of dough in fundamental rheological measurements since small amplitude measurements generally do not give good correlations to baking quality. Stress relaxation gave the most useful information about flour quality through its relaxation spectra. Flours with high total polymeric protein percentages could be identified through their higher relaxation spectra. Starch gelatinization properties of the flours were different for RVA and rheometer temperature sweeps. All of these tests have helped characterize the four Kansas wheat cultivars chosen for this study.
Keywords: Rheology; Wheat; Dough; Rheometer; Agriculture, Agronomy (0285); Agriculture, Food Science and Technology (0359); Agriculture, General (0473)